IN SILICO, IN VITRO AND IN VIVO STUDY OF BAWANG DAYAK (ELEUTHERINE BULBOSA (L) MERR.) POTENTIAL AS ANTI-CHOLESTEROL - ELISA, NOVI; ADVISTASARI, YUSTISIA DIAN; KUSMITA, LIA; PRATIWI, MUSTIKA ENDAH; TOBI, CLAUDIUS HENDRAMAN BOLI (International Journal of Applied Pharmaceutics, 2025)
Objective: This study aimed to determine the potential of Bawang Dayak extract as an anti-cholesterol. Methods: In silico study was carried out using Gas Chromatography-Mass Spectroscopy (GC-MS) analysis and continued with screening using Lipinski’s Rule of Five. In vitro study was carried out using a cholesterol reagent that read in Multimode Reader. In vivo study was carried out by cholesterol level measurement against egg yolk-induced rats. The doses chosen by initial dose orientation and prior efficacy study of Bawang Dayak extract anti-cholesterol effect. Results: The results of in silico study using the Lipinski's Rule of Five was active compound in Bawang Dayak was Undecanoic Acid. Undecanoic acid is ethyl ester compound with Log P<5. Molecular validation produced reference ligand compounds on the IHW9 receptor. Based on previously oriented concentrations and doses, the highest percentage of cholesterol decrease was at 50 ppm (40.04 %) in vitro, and 250 mg/70 kgBW (24.70 %) in vivo. Conclusion: Bawang Dayak has an activity as anti-cholesterol that proven by in silico, in vitro and in vivo study. The absence of evaluation focused on mechanistic studies and anti-cholesterol pathways becomes limitation of this study.